Bayesian semiparametric modeling for HIV longitudinal data with censoring and skewness - Castro, L.M.; Wang, W.-L.; Lachos, V.H.; Inácio de Carvalho, V.; Bayes, C.L. (SAGE Publications, 2019)
In biomedical studies, the analysis of longitudinal data based on Gaussian assumptions is common practice. Nevertheless, more often than not, the observed responses are naturally skewed, rendering the use of symmetric mixed effects models inadequate. In addition, it is also common in clinical assays that the patient’s responses are subject to some upper and/or lower quantification limit, depending on the diagnostic assays used for their detection. Furthermore, responses may also often present a nonlinear relation with some covariates, such as time. To address the aforementioned three issues, we consider a Bayesian semiparametric longitudinal censored model based on a combination of splines, wavelets, and the skew-normal distribution. Specifically, we focus on the use of splines to approximate the general mean, wavelets for modeling the individual subject trajectories, and on the skew-normal distribution for modeling the random effects. The newly developed method is illustrated through simulated data and real data concerning AIDS/HIV viral loads.
Keywords: Skewness; Bayesian probability; Covariate; Computer science; Econometrics; Semiparametric regression; Wavelet; Censoring (clinical trials); Semiparametric model; Random effects model; Longitudinal data; Statistics; Mathematics; Parametric statistics; Data mining; Artificial intelligence; Medicine; https://purl.org/pe-repo/ocde/ford#1.01.03